INVENTARISASI PELAKSANAAN PROGRAM REMEDIAL PADA MATA PELAJARAN BIOLOGI DI SMA NEGERI KOTA PEKANBARU - Panjaitan, Wulan Cristina; Febrita, Elya; Syafi’i, Wan (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstrak : This research aimed to determine the inventory of remedial programs implementation on Biology subjects High School in Pekanbaru in June to November 2018. This type of research is a descriptive study. The population in this study is all State High Schools in Pekanbaru. The research sample is the State High School that has implemented the 2013 curriculum from 2014 is SMAN 1,SMAN 2, SMAN 6, SMAN 8 and SMAN 12. The research instrument consists of closed questionnaires, interview sheets and RPP documents for biology subjects. Data collection techniques are questionnaires distributed during MGMP activities and interviews with biology teachers in Pekanbaru High School. Data analysis techniques are carried out in descriptive percentage. Based on the results of an inventory of the remedial program implementation on Biology subjects High School in Pekanbaru, it has been carried out with an average value of 66, 92% in the good category. The inventory of remedial implementation consists of teacher knowledge in implementation of remedial programs with an average percentage of 72.8%, which is in the good category, while the implementation of remedial programs is an average value of 64.9% with good categories. This implementation consists of planning indicators of 65.93% with good categories. Implementation is 61.9% with good category and evaluation is 67.06% with good category. Based on the results obtained, it can be concluded that the implementation of the remedial program on Biology subjects High School in Pekanbaru has been carried out even though the implementation is still not optimal and not in accordance with the remedial program manual.Keyword : Biology, Inventory, Remedial Programs